2017
DOI: 10.1109/tdmr.2017.2733519
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Failure Analysis of UHF RFID Passive Tags Under Thermal Storage

Abstract: This paper proposes to study the effects of thermal storage on the reliability of passive UHF RFID tags. Two types of tags M1 and M2 from two different manufacturers are aged under two high temperatures equal to 413 K and 433 K. Tested tags are put into a thermal storage oven hang fixed terms. The performances of these tags are measured after each aging phase to determine the power loss caused by the high temperature storage. Then a mathematical approach is used to estimate for both tags from the two manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The four groups were exposed to different stress times at the highest temperature (soak times t s ), while all other parameters remained the same. A first observation is that all tags survive temperature excursions up to 300 • C. This is considerably higher than previous works report for earlier-generation RFID tags with larger coils [7] - [9]. Most of these data further indicate that a longer soak time increases the probability of device failure.…”
Section: A Ramped Temperature Testsmentioning
confidence: 77%
See 2 more Smart Citations
“…The four groups were exposed to different stress times at the highest temperature (soak times t s ), while all other parameters remained the same. A first observation is that all tags survive temperature excursions up to 300 • C. This is considerably higher than previous works report for earlier-generation RFID tags with larger coils [7] - [9]. Most of these data further indicate that a longer soak time increases the probability of device failure.…”
Section: A Ramped Temperature Testsmentioning
confidence: 77%
“…In this work, failure of the RFID tag is defined as a faulty returned code or no response to a readout request. Other published functionality criteria for RFID tags include the power threshold for an RFID tag to respond [7], power of the returned signal [9], or its maximum read range at given read power [10]. True loss of functionality will depend heavily on the application.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature it was reported that during high-temperature cycling tests damage of the tested RFID tags was due to cracks between a pad and an antenna layer [36]. In another study [37] it was found that improper work of the tested RFID tags was caused by cracks in the antenna layer. Furthermore, changes in a chip to antenna attachment material can be taken place what may cause variation in the impedance matching between chip and antenna.…”
Section: Resultsmentioning
confidence: 99%
“…The different parameters: Failure rate (Lambda), MTBF (Mean Time Between Failures) and MTTR (Mean Time To Repair) provide valuable information for system design and maintenance. The reference [10] describes reliability studies carried out on RFID tags, the performance of two tags of two manufacturers aged in temperature storage were compared. These various steps make it possible to validate the study of the component in its mission profile, thus meeting the requirements of the user, but also to extract and analyze the physical defects at the origin of degradations of its characteristics.…”
Section: Reliability and Failure Analysis Study Procedures Of Next-genmentioning
confidence: 99%